ANALISIS TEOLOGIS PEDAGOGIK TERHADAP PRAKTIK BEROIKUMENE DI INSTITUT AGAMA KRISTEN NEGERI (IAKN) TORAJA - Deni Baso’ (JOURNAL OF COMMUNITY DEDICATION, 2023)
Ecumenical means living together in mutual understanding. Living together in a sense that must cover the entire denomination of the church without seeing differences in views that result in a misunderstanding. The fact in the field is that people often blame each other for the differences that exist, this situation of blaming each other creates a division. How can the church be together as one body of Christ if they continue to blame each other, not accept the differences. What must be discussed is how to take the divisions together. The Toraja State Christian Institute as a theological education institution actually has the opportunity to build this unity because at the Toraja IAKN there are various church denominations being discussed together. The important thing that needs to be seen is how the Toraja IAKN functions as a forum that can accommodate all church denominations. As a start, in the future these leaders, religious teachers and prospective priests will return there, when IAKN Toraja teaches ecumenical well. The type of research used in this study is a qualitative approach with data collection through observation, interviews and literature review. From the results of this study, it can be said that the Toraja State Christian Institute has not carried out optimally education towards ecumenical and has not fully implemented the practice of ecumenical life.